Revalidation of Triatoma bahiensis Sherlock &serafim, 1967 (Hemiptera: Reduviidae) and phylogeny of the T. brasiliensis species complex - Mendonca, Vagner José; Alevi, Kaio Cesar Chaboli [UNESP]; Pinotti, Heloisa [UNESP]; Gurgel-Goncalves, Rodrigo; Pita, Sebastián; Guerra, Ana Leticia [UNESP]; Panzera, Francisco; De Araujo, Renato Freitas; De Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; Da Rosa, Joao Aristeu [UNESP] (Magnolia Press, 2016)
Triatoma bahiensis Sherlock &Serafim, 1967, T. lenti Sherlock &Serafim, 1967, and T. pessoai Sherlock &Serafim, 1967 were described based on material collected in the Brazilian state of Bahia. These species were later included in the T. brasiliensis complex based on their geographic distribution. Triatoma bahiensis and T. pessoai were subsequently synonymized with T. lenti. However, the phylogenetic position of T. lenti within the T. brasiliensis complex has remained doubtful. This study aims to assess the taxonomic status of T. bahiensis and to infer the phylogenetic relationships between T. lenti, T. bahiensis and the other members of the T. brasiliensis species complex. The identities of the species in concern were confirmed by comparisons with high resolution photos of the respective type materials; lectotypes are designated for T. pessoai and T. bahiensis. Morphological, morphometric, molecular, and cytogenetic approaches as well as experimental crosses were used. The low viability of experimental crosses combined with morphological and morphometric data allow the differentiation of T. bahiensis and T. lenti. Pairwise cyt b sequence divergence between T. lenti and T. bahiensis was 2.5%. Cytogenetic and molecular analyses grouped T. lenti and T. bahiensis as members of the T. brasiliensis complex. These results revalidate the specific status of T. bahiensis.
Keywords: Chagas' disease vectors; Experimental crosses; Morphology; Taxonomy; Triatominae